Essential oils inhibit the mycelial growth of Fusarium solani - Nascimento, D. M. [UNESP]; Batista, T. B. [UNESP]; Kronka, A. Z. [UNESP]; Vieira, G. H.C. (My University, 2016)
Sudden death syndrome of soybean has caused serious problems in the culture. The aim of this study was to evaluate the effect of essentials oils of copaiba, neem, basil, mint and pink palm on mycelial growth of Fusarium solani f.sp. glycines, which causes this disease. It was tested four concentrations of essential oils, 4000, 6000, 8000 and 10000 µL/L of PDA medium (potato-dextrose-agar). Mycelium discs of 3 mm diameter were inoculated in the center of Petri dishes containing PDA medium with the treatments, and measurements of mycelial growth were perfomed at seven days after the establishment of the experiment. Except for neem and copaiba, the other essential oils completely inhibited mycelial growth. These results showed the antifungal potential of some essential oils in controlling this disease.
Óleos essenciais inibem o crescimento micelial de Fusarium solani
Keywords: alternative control; soybean; sudden death syndrome